PEMANFAAT TEKNOLOGI DIGITAL BERBASIS ANDROID UNTUK PEMANTAUAN STOK AKHIR DALAM PROSES STOK OPNAME PADA UMKM SYARIAH - Surya Darma (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Micro, small, and medium enterprises (MSMEs) play an important role in the Indonesian economy. However, MSMEs still face various challenges, one of which is the inaccuracy in stock management. This can lead to financial losses and reputational damage for MSMEs. Android-based digital technology can be a solution to this problem. Android-based stock management applications can help MSMEs to manage their stock accurately and efficiently. These applications can be used to record stock data in real-time, create stock reports, and provide warnings if stock levels are approaching depletion. This study aims to analyze the utilization of Android-based digital technology for monitoring the final stock in the stock taking process at Shariah MSMEs. This study uses a qualitative method with a case study approach. The results of the study show that the utilization of Android-based digital technology can improve the accuracy and efficiency of stock management in Shariah MSMEs.